A Scoping Review of Risk Factors and Implantation Sites in Ectopic Pregnancy - Halfie Zaqiyah Gusti Puspitasari; Agung Subakti Nuzulullail; Dwina Oktavia Deli; Elsi Dwi Hapsari; Wiwin Lismidiati (Universitas Muhammadiyah Semarang, 2026)
Ectopic pregnancy Ectopic pregnancy is an obstetric condition with serious clinical consequences. This study aims to map the risk factors and location of ectopic pregnancy implantation based on the latest evidence. The design of this study is a scoping review with literature searches conducted on May 20–23, 2025, through ScienceDirect, PubMed, Web of Science, and ProQuest. Inclusion criteria included open-access original articles published between 2020 and 2025 that reported risk factors and implantation sites for ectopic pregnancy. Theoretical articles and instrument development studies were excluded. The selection and synthesis process followed the PRISMA-ScR (2020) guidelines, the JBI Critical Appraisal Checklist (2020), and the Guidance for Conducting Systematic Scoping Reviews (2015). Of the 5,519 articles identified, eight studies with observational (n=7) and cross-sectional (n=1) designs met the criteria. The synthesis results showed that a history of previous ectopic pregnancy was the most consistently reported risk factor, followed by a history of surgery and infertility. The most common implantation site was the fallopian tube, particularly in the ampulla, fimbria, and isthmus. These findings emphasize the importance of comprehensive identification of risk factors to support more effective prevention, early detection, and long-term management strategies